Neural activations associated with feedback and retrieval success. (December 2017) - Wiklund-Hörnqvist, Carola; Andersson, Micael; Jonsson, Bert; Nyberg, Lars
Abstract There is substantial behavioral evidence for a phenomenon commonly called "the testing effect ", i.e. superior memory performance after repeated testing compared to re-study of to-be-learned materials. However, considerably less is known about the underlying neuro-cognitive processes that are involved in the initial testing phase, and thus underlies the actual testing effect. Here, we investigated functional brain activity related to test-enhanced learning with feedback. Subjects learned foreign vocabulary across three consecutive tests with correct-answer feedback. Functional brain-activity responses were analyzed in relation to retrieval and feedback events, respectively. Results revealed up-regulated activity in fronto-striatal regions during the first successful retrieval, followed by a marked reduction in activity as a function of improved learning. Whereas feedback improved behavioral performance across consecutive tests, feedback had a negligable role after the first successful retrieval for functional brain-activity modulations. It is suggested that the beneficial effects of test-enhanced learning is regulated by feedback-induced updating of memory representations, mediated via the striatum, that might underlie the stabilization of memory commonly seen in behavioral studies of the testing effect. Neuroscience: Test-enhanced learning with feedback Repeated testing with feedback shapes functional brain activity and strengthens new learning. A team led by Carola Wiklund-Hörnqvist at Umeå University, tracked brain activity in humans while being repeatedly tested with or without feedback. Higher hippocampal activity was found for feedback compared to no feedback, and learning from feedback was related to increased activity predominantly in the insula. For retrieval success, up-regulated activity in fronto-striatal regions was evident at the first successful retrieval with a marked decrease across consecutive tests. Those results indicate that while both feedback and retrieval success are key aspects that foster the "testing effect"; they operate at different functional levels in the brain. Future studies are needed to further explore the efficiency of test-enhanced learning in relation to individual variation in cognitive proficiency.